CONCEPTUAL PRINCIPLES OF SUSTAINABLE RURAL DEVELOPMENT CONSIDERING FINANCIAL AND SOCIAL COMPONENTS - Pasichnyk, Yurii; Sukach, Olena (Current Problems of Sustainable Development, 2026)
The article examines the theoretical and methodological foundations for ensuring the sustainable development of rural territories under the conditions of postmodern transformations, wartime challenges, and European integration processes in Ukraine. It is substantiated that the current state of rural territories is characterized by increasing structural disparities, depopulation, deterioration of social infrastructure, a low level of economic diversification, and insufficient financial self-sufficiency of territorial communities. It has been established that traditional approaches to rural development, primarily focused on agricultural production, have exhausted their potential and fail to ensure the systemic sustainability of territories, as they insufficiently account for social, institutional, and spatial development factors. Based on the research findings, the expediency of revising theoretical and methodological approaches to sustainable development through the integration of financial self-sufficiency instruments, mechanisms of social reproduction, and institutional interaction has been substantiated. A synergistic model of sustainable rural development is proposed, based on the mutual reinforcement of financial-economic, socio-humanitarian, institutional-managerial, and spatial resilience components. It is proved that the financial stability of territorial communities should not be regarded as an end in itself but rather as an instrument for enhancing social security, developing human capital, and increasing the investment attractiveness of territories. It has been established that the synergistic effect of the proposed model is manifested through a mechanism of positive self-reinforcement, whereby the financial autonomy of a community contributes to the development of social infrastructure, entrepreneurship, and human potential, thereby ensuring the long-term sustainability of rural territories. The practical significance of the study lies in the possibility of applying the proposed approaches in the development of local development strategies, the improvement of fiscal decentralization mechanisms, and the implementation of post-war recovery programs for rural territories in Ukraine